Giant Omphalocele with skeletal deformities: a case report - Meshram, Rajkumar M.; Phatak, Amruta; Bhurke, Arvind; Chaudhari, Chetan (International Journal of Contemporary Pediatrics, 2018)
Omphalocele is an anterior abdominal wall defect at the base of the umbilical cord, with herniation of the abdominal contents which are covered by a membrane and associated with a very high incidence of structural and chromosomal anomalies including heart defect, vesical, genital or diaphragmatic malformations. A 1000 gm preterm neonate was born vaginally, to a non-consanguineously married primi mother with uneventful pregnancy. On examination baby had a large anterior abdominal wall defect covered by a thin membrane with widely open and bulging anterior fontanellae. Eyes, ears and lips were well developed but eyelids were fused. Liver, spleen and intestine were visible under a thin transparent membrane. Rib cage was formed, and ribs were palpable but lower limbs were directed posteriorly and genitalia was ambiguous. Baby was in gasping condition and died within 30 minutes after birth. Prenatal accurate diagnosis by providing adequate antenatal care and ultrasonogram would permit an opportunity to counsel the family and to prepare for optimal postnatal care.